Marker Assisted Selection Applications in Farm Animals - KEPEZKAYA, Ali; BOGA, Yunus Emre; ÇİMEN, Ömer (MAS Journal of Applied Sciences, 2024)
Recent advances in molecular genetics have been of great importance in the selection process of livestock and in increasing the rate of genetic progress. Especially molecular markers have found a wide range of applications in the livestock sector. Molecular markers play an important role in determining the desired yield characters of animals, in parentage determination and in the control of genetic diseases.One of the most important applications of molecular markers is genomic selection. This application analyzes the genetic structure of animals at the molecular level to predict their potential to exhibit desired traits. In this way, it is possible to select breeding animals more accurately and quickly than traditional methods based solely on phenotypic traits. The use of molecular markers can overcome the limitations of traditional breeding methods and accelerate the selection process for traits of economic value. In conclusion, advances in molecular biology and applications of molecular markers in the livestock sector can make significant contributions to the national economy by enabling the genetic potential of animals to be increased more rapidly. These technologies can open the doors to further innovations and developments in animal breeding and livestock management in the future.